Roles in Research Teams: The Perspective of University Commercialisation - Zastempowski, Maciej; Kalocińska-Szumska, Aleksandra; Łaskowska, Justyna (Zielona Góra: Faculty of Economics and Management Press)
Although the investigation of team roles has been a focus of scientific research over an extended period, one of the less recognised issues in this area is the functioning of research teams, especially in commercialising their scientific results. Drawing from a comprehensive examination of the literature and the concept of "The A-to-F Model" by de Bes and Kotler, this paper aims to broaden the knowledge about the research team`s roles and their influence on commercialising their results.
Keywords: research teams; team roles; commercialisation; innovation